An Integrated Cutting Tool Selection and Operation Sequencing Method - Rho, H.M.; Geelink, R.; van, 't Erve A.H.; Kals, H.J.J. (1992)
Summary: Within the P.%RT C'APP system. the selection of an optimum operation sequence is related to the modules which perform the machining method and cutting tool selection. This study analyzes the technical and economical aspects of operation sequencing and presents a method which is capable of generating an optimum solution on the basis of previously selected machining operations and alternative cutting took per operation. Precedence relations between operations provided by the method selector are used as constraints which should not be violated. The operation sequencing method simultaneously assigns single tools from a list of alternatives to each operation and manipulates the operation sequence in order to minimize the total number of toolchanges and the number of required tools. ？ 1992 CIRP.
Keywords: Computer aided analysis; Metal working; Process engineering; Selection; Computer automated process planning (CAPP); Machining method selection module; Planning of activities, resources and technology (PART); Tool selection module; Cutting tools